2019
DOI: 10.1161/circheartfailure.118.005529
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of RNA Polymerase II to Metabolic Gene Promoters Is Inhibited in the Failing Heart Possibly Through PGC-1α (Peroxisome Proliferator-Activated Receptor-γ Coactivator-1α) Dysregulation

Abstract: Background: Proper dynamics of RNA polymerase II, such as promoter recruitment and elongation, are essential for transcription. PGC-1α (peroxisome proliferator-activated receptor [PPAR]-γ coactivator-1α), also termed PPARGC1a, is a transcriptional coactivator that stimulates energy metabolism, and PGC-1α target genes are downregulated in the failing heart. However, whether the dysregulation of polymerase II dynamics occurs in PGC-1α target genes in heart failure has not been defined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 18 publications
1
38
0
Order By: Relevance
“…Some reports have suggested that downregulation of PGC-1α is a major cause of mitochondrial impairment and metabolic defects in the failing heart (7,8,21,22). However, other studies, including ours, suggest that the expression levels of PGC-1α per se cannot always explain downregulation of PGC-1α target genes in the failing heart (23)(24)(25). In this review, we carefully analyze recent findings in an attempt to construct a holistic picture of the complex mechanisms contributing to impaired PGC-1α regulatory function in the failing heart.…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…Some reports have suggested that downregulation of PGC-1α is a major cause of mitochondrial impairment and metabolic defects in the failing heart (7,8,21,22). However, other studies, including ours, suggest that the expression levels of PGC-1α per se cannot always explain downregulation of PGC-1α target genes in the failing heart (23)(24)(25). In this review, we carefully analyze recent findings in an attempt to construct a holistic picture of the complex mechanisms contributing to impaired PGC-1α regulatory function in the failing heart.…”
Section: Introductionmentioning
confidence: 53%
“…However, the dynamics of PGC-1α expression in the failing heart may be more complex. In animal models of failure, most of the studies showed downregulation of PGC-1α (8,(51)(52)(53)(54)(55)(56)(57), but some studies found no change (24,25,58). Likewise, analysis of tissue samples obtained from patients at the advanced stage of heart failure showed a variability of outcomes, including decreased gene (59) or protein (60) expression, unchanged gene expression (61,62), or even a slightly increased gene expression of PGC-1α (63).…”
Section: Pgc-1α Expression In Heart Failurementioning
confidence: 99%
See 3 more Smart Citations